Between in- and re-action: Resistance and resilience in Stefan Zweig’s Erasmus of Rotterdam (Altre Modernità, 2022)
This article provides a reading of Stefan Zweig’s auto/biography Erasmus of Rotterdam (1934) as the writer’s counteraction to a situation of vulnerability and conflict. Erasmus does not just fall within the genre of the historical biography, but it also represents a “veiled autobiography” in that, by depicting a kindred soul of his, Zweig exposes himself unreservedly to the world. In contrast to most of the studies conducted so farmainly focused on the author’s implicit confession of faintheartedness through his literary alter-egothis contribution aims to demonstrate that it is not the idea of escapism, but rather that of resistance/resilience, that underpins the text. To this end, the affinities between Zweig and Erasmus in terms of their common marginality and vulnerability will be explored, in order to better understand their personal response to this status, that is, a peaceful fight carried out by means of poetic acts. According to this perspective, Zweig’s Erasmus-biography will be presented as a re-action in two different ways: on the one hand the autobiographical references disclose the writer’s concerns about National Socialism, turning his work into an artistic form of dissidence, i.e., a practice of resistance; on the other hand, the therapeutic function ascribed by Zweig to the text composition unveils it as a testimony of resilience.